New technologies, Social Media and Democracy - Edilene Lôbo; José Luis Bolzan de Morais (Opinión Jurídica)
This article aims to consider the impact of new technologies in the Brazilian elections of 2018, questioning about the possibilities of its transformation with the prominent use of social networks to directly connect citizens and candidates, without the customary intervention of political parties and traditional media. It also aims to discuss the role of fake news in the electoral process and the means to fight it, so it does not denature the free thought formation as a human right essential to the practice of citizenship in the new digital age.